DOF Enhanced via the Multi-Wavelength Method for the Moiré Fringe-Based Alignment - Kairui Zhang; Haifeng Sun; Dajie Yu; Song Hu; Junbo Liu; Ji Zhou (Micromachines)
Alignment systems are core subsystems of lithography, which directly affect the overlay accuracy of the lithography process. The Moiré fringe-based alignment method has the advantages of high precision and low complexity. However, the precision of this method is highly sensitive to variations in the gap between the wafer and the mask. To enhance the performance of Moiré fringe-based alignment, this paper proposes a novel method in which the multi-wavelength approach is used to enhance the imaging depth of focus (DOF). We use a multi-wavelength light to illuminate the alignment marks on the wafer and mask, which is combined with different sources. Then, we use the improved phase analysis algorithm to analyze the contrast of the Moiré fringe and calculate the Moiré fringe displacement. Experiments show that, in an alignment range of 1000 μm, the effective DOF can exceed 400 μm. It is evidenced that the accuracy of the Moiré fringe alignment is unaffected and remains at the nanometer level. Otherwise, with parameter optimization, the alignment DOF is expected to be further extended.